Relationships between diffusion of innovation factors and acceptance of the 1Malaysia concept - Manan, Juliana (2013)
It is essential that Malaysian understand the concept of 1Malaysia that was introduced by the government. The aim of the study was to examine the relationship between the Diffusion of Innovation factors and the acceptance of the Malaysian public towards the ‘1Malaysia’ concept introduced by the sixth Prime Minister, Dato’ Sri Mohd Najib bin Tun Hj Abd Razak. Specifically the study was conducted to examine whether i) there is a significance difference in the level of knowledge on the 1Malaysia concept by ethnic groups ii) there is a significance difference in the level of understanding on the 1Malaysia concept by ethnic groups iii) there is a significance difference in the perception towards the 1Malaysia concept by ethnic groups iv) there is a significance difference in the level of acceptance on the 1Malaysia concept by ethnic groups v) the relationship between the level of knowledge and the level of acceptance of the 1Malaysia concept vi) the relationship between the level of understanding and the level of acceptance of the 1Malaysia concept and vii) the relationship between the perception and the level of acceptance of the 1Malaysia concept. A survey was conducted involving 500 respondents selected from those residing in the urban and sub-urban areas in the ,Klang Valley. The respondents were selected through a non-random quota sampling to response a self-administered specifically designed questionnaire as a study instrument. Descriptive Statistics, Pearson Product-Moment Correlation, and one-way ANOVA test were used to analyze the data. The findings resulted that there is a significant differences in terms of ethnic group towards the level of understanding, perception and acceptance on the 1Malaysia concept, except for the level of knowledge on the 1Malaysia concept. In addition, the findings also indicated there was a positive relationship between the level of acceptance of the 1Malaysia concept with the level of knowledge, level of understanding and perception towards the 1Malaysia concept. Televisions are the main sources mass media channel in which most respondents were exposed to the 1Malaysia concept information with duration of 30 minutes to one hour time per day. This study suggests that besides continuous publicity, it is important for the government departments and agencies to conduct seminars, workshops and briefings and other service training to provide accurate information related to the 1Malaysia concept. Finally, this study should be replicated to determine other constructs or factors that would influence the level of acceptance of the 1Malaysia concept.